Pengaruh Latihan Target Hasil Ketepatan Shooting Menggunakan Kaki Bagian Dalam pada Permainan Futsal Club Putra Prabu - Juliandri, Romy; Lubis, Patricia H.M; Hermansyah, Bambang (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
Every player in a game always has his own way to win a match, players have tricks as well as speed and accuracy, including shooting accuracy using the inside of the foot in the game of futsal. The purpose of this training is to improve shooting accuracy using the inside of the foot in futsal.This research method is a quantitative research with a quasi-experimental design approach orquasi-research. The subjects in this study were Club Putra Prabu totaling 20 people. The samplingtechnique in this study was using a saturated sampling technique. The data collection techniquethat will be used is using field performance techniques or futsal shooting practices, and using the field, goal, meter, raffia string to divide the target shooting scores as the results achieved by the players. Based on the results of research that has been conducted on the athletes of the PutraPrabu Futsal Club, the average results of the pretest are 21.8 and the average post-test is 25.5, it shows that the effect of target training on shooting accuracy can increase the potential results of athletes' skills. in improving shooting results well. Because there is an increase after being given treatment compared to before being given treatment or treatment. In testing the hypothesis, the value of t-count > t-table or 22.35 > 1.73, so it can be concluded that there is an effect of target training on the accuracy of shooting using the inner foot of the Putra Prabu Futsal Club players.